ملة إبراهيم - رؤية قرآنية = Millah Ibrahim - Quranic perspective - Al-'Abdali, Khalid Muhammad; Mamat, Ismail (The Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This article aims to explain about Millah Ibrahim (peace be upon him) from Quranic perspective. Basically it is a guidance and happiness for humanity. Allah SWT ordered His Messenger, Muhammad (peace be upon him) and his Ummah to follow it. This is the way that Ibrahim (Peace be upon him) was to deny polytheism (shirk) of all kinds, and to avoid idolatry in all its forms. It is also the way in his call and argument of his people, and in the work of Hajj, and in his declaration of innocence of polytheism and polytheists and how to reach the peak of faith and ideal that should be followed. The sacrifices and works done by Ibrahim (peace be upon him) are the models to be followed which demonstrated the sincerity of attachment to the commands of God Almighty. The features of Millah Ibrahim (peace be upon him) can be seen in his struggle and his diligence in communicating the religion of Allah, with the attendant of charity (iḥsān) and sincerity (ikhlās). Its fruit, which Allah SWT promised, obtained happiness in this world and the hereafter.